Upsurge of Rodents' Population in a Rural Area of Northeastern Iran Raised Concerns about Rodent-borne Diseases - Ahmad Ghasemi; Saber Esmaeili; Abdolrazagh Hashemi Shahraki; Hamed Hanifi; Zeinolabedin Mohammadi; Ahmad Mahmoudi; Mahdi Rohani; Ehsan Mostafavi (Pasteur Institute of Iran, 2017)
Introduction: Rodents are the primary source of several zoonotic infectious diseases. The upsurge of rodents' population in Najaf Abad Village of Nishapur County, northeastern Iran in February 2014 raised the concerns about the outbreak of diseases such as plague and tularemia. This report discusses the lessons learned from the outburst of rodents' population in that village and represent as well the investigations performed by a dispatched team from Pasteur Institute of Iran for detection of potentially pathogenic agents in the entrapped rodents. Methods: In this study, different areas of Najaf Abad village were explored. The animals were identified based on morphological features using identification keys. Sera from all rodents were tested for plague and tularemia using ELISA and agglutination tests, respectively. Results: Seven captured rodents belonged to the family Muridae Illiger, 1811, and the species, Mus musculus Linnaeus, 1758 (n=4), Meriones libycus Illiger, 1811 (n=2), and Nesokia indica Gray, 1830 (n=1) were identified. All the rodents were negative for plague and tularemia. Conclusion: The outburst rodents' populations in this village that began in 2007 can be attributed to the old structure of the village, drought, and the disappearance of natural predators of rodents. Also, due to drought in the recent years, extensive agriculture was not possible, which might have led to the invasion of rodents to the human settlements. It is recommended that in such events, regular programs to be carried out under the supervision of an organization to achieve the best results in the shortest possible time.